Peran Quadruple Helix Dalam Meningkatkan Kreatifitas Dan Inovasi Industri Kreatif Berbasis Syariah - Ferri Alfadri (ITB AAS INDONESIA Surakarta, 2023)
The purpose of this study to find out how the role of each Quadruple Helix party is in increasing the performance of creativity and innovation in creative industry players in Padangsidimpuan City. This research is a field research with a qualitative method approach with Miles and Huberman descriptive analysis. Data collection techniques were carried out by direct observation and interviews with each of the helix actors. The Result in this study provide a conceptual framework for how creativity can be enhanced through the four helix approaches and interactions to enhance innovation performance. Within this framework, creativity is an important factor to improve the innovation performance of Indonesia's creative industries